USING SUSTAINABLE DEVELOPMENT PRINCIPLES TO ASSESS THE EFFICIENCY OF TRANSPORT INTERCHANGES FUNCTIONING - Samchuk, G.; Самчук, А. А.; Самчук, Г. О. (Харьковский национальный автомобильно-дорожный университет, 2016)
The expediency of using the sustainable development principles for assessing the efficiency of public transport interchange functioning is shown. The passenger waiting time, the probable number of accidents in the area of transport interchanges, the queuing delay, and the amount of total emissions as CO2 equivalent were chosen as indicators that the efficiency criterion includes.
ИСПОЛЬЗОВАНИЕ ПРИНЦИПОВ УСТОЙЧИВОГО РАЗВИТИЯ ДЛЯ ОЦЕНКИ ЭФФЕКТИВНОСТИ ФУНКЦИОНИРОВАНИЯ ТРАНСПОРТНО-ПЕРЕСАДОЧНЫХ УЗЛОВ
ВИКОРИСТАННЯ ПРИНЦИПІВ СТАЛОГО РОЗВИТКУ ДЛЯ ОЦІНКИ ЕФЕКТИВНОСТІ ФУНКЦІОНУВАННЯ ТРАНСПОРТНО-ПЕРЕСАДОЧНИХ ВУЗЛІВ
Keywords: public transport interchange; efficiency criterion; sustainability; indicators; costs; транспортно-пересадочный узел; критерий эффективности; устойчивость; индикаторы; расходы; транспортно-пересадочний вузол; критерій ефективності; сталість; індикатори; витрати; 656.025.2=111